Does the carbon trading mechanism affect social and environmental benefits of the retailer-led supply chain: Strategic decisions of emissions reduction and promotion - Tong, Wen; Liu, Hengyu; Du, Jianbang (Frontiers in Environmental Science, 2022)
Governments, enterprises, and customers become more concerned about environmental protection. Following the world's largest carbon trading market (EU ETS), China has also implemented a market-based carbon trading mechanism (CAT) to reduce CO2. Simultaneously, customers have low-carbon preferences for environmental products. Thus, the enterprises’ strategic decisions and collaboration modes have changed. This paper develops the Stackelberg game model to explore the impacts of CAT and customers’ low-carbon preference on the carbon emissions reduction and promotion strategies in a retailer-led supply chain (such as RT-Mart, Walmart, Amazon, etc.). In this model, the retailer decides whether to promote environmentally products and the manufacturer decides whether to reduce CO2. We find that carbon trading market price and the customers’ low-carbon preference are key factors influencing retail price, total carbon emissions, and social welfare. Interestingly, there is not always a positive correlation between customers’ low-carbon preference and social welfare. To achieve Pareto improvement of social welfare, manufacturer and retailer require co-optimization. Theoretically, our research enriches the research streams of CAT policy and socially responsible operations of the supply chain. Moreover, managerial insights are provided for retailer-led supply chain stakeholders and emission reduction regulators, which contribute to enhancing the social and environmental benefits of supply chains.